Cash Purchase Information System Design - Harrison D S; Fajar Azzam Pasha Akhmad; Aditya Putra Kusuma (Peneliti.net, 2022)
The Mekar Jaya Farmers Cooperative is a business unit that serves farmers in the supply of fertilizers, seeds and various other agricultural needs. This cooperative buys goods in cash from factories and then sells them to farmers using a credit system. The problem that is often faced is the difficulty in controlling the stock of fertilizer and the process of purchasing fertilizer which is still done manually. This causes a shortage of fertilizer stocks. This study tries to develop a solution in the form of a cash purchase information system design, where this system works in managing purchases and automatically counting inventory, this system is also useful for facilitating cash purchase transactions. The designed system is supported by SQL Server 2005 software as a database and Visual Basic 2008 Programming Language as a programming language in the cash purchase system. The results obtained if this system can be implemented are, making it easier for the Mekar Jaya Farmers Cooperative in every cash purchase transaction and making it easier to input goods, making reports that are more accurate than using a manual system and in making decisions if problems occur in the future, and make it easier to report every transaction that occurs to the owner/chairman of the cooperative.